2022
DOI: 10.3390/biom12101448
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR92a Promotes Cytarabine Resistance in Myelodysplastic Syndromes by Activating Wnt/β-catenin Signal Pathway

Abstract: Cytarabine (Ara-C) has been one of the frontline therapies for clonal hematopoietic stem cell disorders, such as myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML), but Ara-C resistance often occurs and leads to treatment failure. Exosomal microRNAs (miRNAs, miRs) as small noncoding RNA that play important roles in post-transcriptional gene regulation, can be delivered into recipient cells by exosomes and regulate target genes’ expression. miR92a has been reported to be dysregulated in many cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In cancer cells, exosome-derived miR-375 targets DIP2C and regulates Wnt signaling, thus promoting osteoblastic metastasis ( 119 ). Li et al ( 120 ) revealed that exosomal miR-92a promotes cytarabine resistance through activating the Wnt/β-catenin signaling pathway ( 120 ). In conclusion, exosomal miRNAs may influence tumor progression through regulating Wnt signaling.…”
Section: Crosstalk Between Exosomal Mirnas and Wnt Signalingmentioning
confidence: 99%
“…In cancer cells, exosome-derived miR-375 targets DIP2C and regulates Wnt signaling, thus promoting osteoblastic metastasis ( 119 ). Li et al ( 120 ) revealed that exosomal miR-92a promotes cytarabine resistance through activating the Wnt/β-catenin signaling pathway ( 120 ). In conclusion, exosomal miRNAs may influence tumor progression through regulating Wnt signaling.…”
Section: Crosstalk Between Exosomal Mirnas and Wnt Signalingmentioning
confidence: 99%
“…In another study of 42 MDS patients, investigators identified five circulating miRNAs, namely miR-423-5p, miR-126-3p, miR-151a-3p, miR-125a-5p, and miR-199a-3p, whose combined expression levels in plasma could predict response to azacytidine therapy [76]. Finally, beyond HMAs, in a recent study, investigators found that overexpression of exosomal miR-92a (member of miR17-92 cluster) in plasma promoted cytarabine resistance in MDS/AML by activating the Wnt/β-catenin signaling pathway, rendering miR-92a both a potential predictive biomarker and a therapeutic target for patients with MDS [89].…”
Section: Mirnas As Potential Predictive Biomarkers Of Response In Mdsmentioning
confidence: 99%